Cardiovascular responses to exercise tests in subjects with poliomyelitis: A pilot study - T. K. Kolapo Hamzat (AOSIS, 2000)
People with physical disabilities often experience difficulty in different activities of daily living. Emphasis is usually placed on their medical rehabilitation, and there is often little attempt on meeting the healthcare needs after they are discharged from rehabilitation facilities. Recognition of the health care needs is required to provide effective treatment and facilitate health promotion activities. Decreased muscle strength in the lower limbs in victims of poliomyelitis often result in difficulties in mobility. As part of a larger study to evaluate the impact of regular aerobic exercise on the quality of life of individuals with physical disabilities, this pilot study attempted to obtain information on some immediate responses to the nine-minute walk/run test among a group of people with physical disabilities due to poliomyelitis. Compared to an age-matched control group, there was a higher cardiovascular demand on individuals with poliomyelitis. The outcome was suggestive of a need to assist the subjects in conserving energy during ambulation by improving endurance. Thus individuals with poliomyelitis are likely to benefit from regular aerobic exercise.